Congress versus the Supreme Court, 1957-1960. - Pritchett, C. Herman (Charles Herman), 1907-1995 (University of Minnesota Press, 1961)
Congress Versus the Supreme Court, 19571960 was first published in 1961. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions. This is an account of the effort made in the last two sessions of Congress to curb the Supreme Court because of certain liberal decisions of the Court, and an analysis of the reasons for the congressional failure. Many times in history Congress has objected to Court decisions and has tried to retaliate against the Court. The most recent period of difficulty traces back to the Court's school segregation decisions in 1954, but not until the Court took a liberal line in certain national security cases in 1956 and 1957 was an organized effort made in Congress to attack it. Professor Pritchett analyzes the specific decisions which aroused congressional concern and reviews the methods by which their reversal was sought. The failure of this effort to curb the Court is important to an understanding of the role of the Supreme Court in the American governmental system. This book is an expansion of the Guy Stanton Ford lectures given by Mr. Pritchett at the University of Minnesota.